Gender, Power, and Health: Measuring and Assessing Sexual Relationship Power Equity Among Young Sub-Saharan African Women and Men, a Systematic Review. (July 2022) - Closson, Kalysha; Ndungu, Jane; Beksinska, Mags; Ogilvie, Gina; Dietrich, Janan J; Gadermann, Anne; Gibbs, Andrew; Nduna, Mzikazi; Smit, Jenni; Gray, Glenda; Kaida, Angela
Gender inequity, including low sexual relationship power (SRP), is an important determinant of intimate partner violence (IPV) and negative sexual, reproductive, and mental health. Different versions of the Sexual Relationship Power Scale (SRPS) are commonly used within youth studies to examine how gender inequities, including controlling behaviors, in heterosexual relationships impact the lives of young people in sub-Saharan Africa. This review aims to (1) describe definitions and measures of SRP within sub-Saharan African youth studies and (2) review and summarize associations between SRP equity, IPV, and sexual, reproductive, and mental health. After searching Pubmed, Ovid Med, Psych info, Web of Science, Google Scholar, and relevant research forums, 304 papers were identified, of which 29 papers based on 15 distinct studies (published 2004–2019) met our criteria for being youth-specific, conducted in sub-Saharan Africa, and including a quantitative measure of SRP. Details of each SRPS are described, including any adaptations and psychometric properties, as well as associations with IPV, sexual, reproductive, and mental health behaviors and outcomes. Results indicate that there are variations to the SRPS, and a paucity of evidence has detailed the psychometric properties of such measures within sub-Saharan African youth studies. Measures of SRP equity are associated with experiences (among women) and perpetration of (among men) IPV as numerous pathways to HIV risk; however, the evidence remains mixed. In order to address overlapping epidemics of violence against women and HIV, efforts are needed to ensure that measures, including the SRPS, are valid and reliable among highly affected populations.